(untitled) (Journal of the College of Basic Education, 2026)
This study aims to determine the functional efficacy of a Solution-Focused Brief Therapy (SFBT)-based supervisory program in developing Active Listening and Crisis Intervention skills among counselors in governmental schools within the Salfit Governorate, Palestine. The research utilizes a Single-Case Design (SCD) of the A-B type. The sample includes a single counselor (N=1) practicing in the Salfit Governorate. Data collection is conducted using an objective performance observation card administered over a total of ten (10) repeated measurement sessions. The findings reveal the achievement of an ideal effect size (U = 1.00) for both Listening and Intervention skills. This unequivocally establishes a functional relationship and demonstrates the program’s exceptional efficiency in achieving an immediate performance improvement. Based on this demonstrated efficacy, the study recommends integrating the Solution-Focused supervision model into intensive training programs for developing the essential functional skills of school counselors. This study aims to determine the functional efficacy of a Solution-Focused Brief Therapy (SFBT)-based supervisory program in developing Active Listening and Crisis Intervention skills among counselors in governmental schools within the Salfit Governorate, Palestine. The research utilizes a Single-Case Design (SCD) of the A-B type. The sample includes a single counselor (N=1) practicing in the Salfit Governorate. Data collection is conducted using an objective performance observation card administered over a total of ten (10) repeated measurement sessions. The findings reveal the achievement of an ideal effect size (U = 1.00) for both Listening and Intervention skills. This unequivocally establishes a functional relationship and demonstrates the program’s exceptional efficiency in achieving an immediate performance improvement. Based on this demonstrated efficacy, the study recommends integrating the Solution-Focused supervision model into intensive training programs for developing the essential functional skills of school counselors.